Challenges on Standardized Diabetes Mellitus Care Implementation in the Primary Health Care in Indonesia: A Narrative Review - Arnita Sofianingrum; Sutopo Patria Jati; Martini Martini (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The prevalence of diabetes mellitus remains high worldwide and has long-term health implications and impacts on the quality of life of those affected. As a catastrophic disease, diabetes mellitus has the potential to burden national healthcare financing, including in Indonesia. Improving standardized diabetes mellitus services, starting from primary healthcare facilities, is a critical effort that is hoped to address this potential burden. The aim of this study is to synthesize and obtain information on the challenges of implementing minimum standards for diabetes mellitus services in Indonesia. Method: This study is a narrative literature review using the PRISMA framework. In this review, inclusion and exclusion criteria to gather articles from Pubmed, ScienceDirect, Google Scholar, ProQuest, and Emerald. The MMAT instrument was used to select eligible articles in study. Results: Our findings indicate that 19 eligible journal articles related to the challenges of implementing minimum standards for diabetes mellitus services in Indonesia. The synthesis results showed that there are challenges in implementing minimum standards for diabetes mellitus services in Indonesia, particularly in the internal and external aspects of patients, primary healthcare facilities, and the government. Conclusions: The challenges of implementing minimum standards for diabetes mellitus services in Indonesia need to be addressed through enhancing the interpersonal and practical skills of healthcare providers, strengthening the role of primary healthcare facilities and the government, ensuring adequate funding support, and establishing appropriate indicators that reflect the field's conditions as a reference for achieving the implementation of minimum standards for diabetes mellitus services in Indonesia.